The Role of International Law in Ensuring The Right to Education in Developing Countries - Duerawee, Abdulkarim (International Journal of Law and Legal Ethics, 2025)
International law has guaranteed the right to education through various legal instruments; however, its implementation in developing countries still faces serious obstacles due to economic, social, political, and cultural factors, leading to significant disparities in access to and quality of education. This study aims to examine the role of international law in ensuring the right to education in developing countries. A qualitative approach using literature review is employed to analyze the effectiveness of international law in guaranteeing the right to education in these countries. A descriptive-analytical analysis and a comparative study with Thailand are used to identify gaps and solutions for implementing education policies. The findings indicate that the role of international law includes affirming the right to education through various legal instruments, despite persistent challenges in developing countries, such as budget constraints and unequal access. International organizations play a crucial role in supporting global education policies, while Thailand serves as an example of a more progressive country in aligning its policies with international standards. To enhance the effectiveness of international law, stricter monitoring, sanctions for non-compliant states, and global cooperation in providing educational resources are necessary.